Uncertainty of atomic force microscopy measurements - Gotszalk, Teodor P.; Janus, Paweł; Marendziak, Andrzej; Szeloch, Roman F. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
We consider the problem of uncertainty in geometrically linear measurements in scanning probe microscopy (SPM) represented by atomic force microscopy (AFM). The uncertainties under consideration are associated both with quantum phenomena in the space cantilever tip–sample surfaces and with effects of dynamic behavior of electronic and optic measurement and control systems. In our experiment, we have analyzed uncertainty of calibrated atomic force microscopy (C-AFM) measurement in two dimensions. Uncertainty of measurements has been estimated according to GUM procedure.
Optica Applicata, Vol. 37, 2007, nr 4, s. 397-403
Keywords: optyka; uncertainty of measurement; atomic force microscopy (AFM)